Toponymie : « Contribution à la dialectologie bretonne » - Jean-Marie Plonéis (La Bretagne Linguistique, 1992)
In simple polysyllabic words or derivatives, KLT Breton (Cornouaille, Léon, Trégor) is stressed on the penultimate syllable, a fundamental difference from the Pays-Vannetais Breton which is stressed on the last syllable. Between these two main variants of Breton, we have an intermediate zone which, starting from the east of Quimper by the south of Carhaix, runs as far as Tréguier, a zone where the variants of the Vannetais type become rarer, the further one moves away from the Gulf of Morbihan. However, a detailed study of the names of plots in the nine communes of the Monts d’Arrée reveals particularities of the Vannetais type in the toponymy which are never used in the local language.